Analysis of Symbols Authority through the Perspective of Islamic Holistic Study - Salsabila, Unik Hanifah; Aziizah, Aabidah Ummu (Journal of Islam and Science, 2020)
The fundamental dialectical theory of the Berger model claims that humans are a product of society and society is a human product, so both require interaction and dialectics to influence each other in social life. Until the scope of the rite, each human is a judge to have a specific social function, if he has the influence to regulate, maintain, and transmit sentiments from one generation to another. In other words, humans will always express their existence through artificial things and a sign for each human being to have connectivity with each other. Even if it reviewed historically, it is not necessarily born from the Islamic body ideologically. How much authorization of tangible symbols on religious practices in the Islamic paradigm? Are material symbols in spiritual practices limited to the manifestation of human creativity or sacred things that cannot contest? This scroll will continue until there is a discussion about it.